Strengthening of regional tourism development by creating tourism clusters in the cities of Ukraine - Bezkhlibna, Anastasiiya; Nykonenko, Svitlana (Univerzita Pardubice, 2017)
In the article it is considered the topical issues of creation of tourist clusters in regions. Tendencies of the international tourism development demonstrates growth of employment in the economy. Functioning of tourist clusters as tourist centers is obviously possible only when there are functioning and harmonious cooperation of systems of tourist attractiveness, transport, service and quality service control, insurance system and support of tourists’ personal security, systems of tourist pointers and tourist infrastructure. There were chosen the following factors of a tourist cluster creation: geographical closeness, demand availability, formation of the general development strategy, hierarchical functional communications between participants. For the purpose of clarifying the relevance of creation of a regional tourist cluster, the estimation algorithm of the ability of its creation was proposed, and it consists of 8 stages. Each stage is detailed. The participants (subjects) of a potential cluster are systematized. SWOT analysis is proposed for determination of drawbacks and advantages of tourist clusters functioning. This will allow to improve work of a cluster participants.
Keywords: regional development; tourism perspectives; partnership; cooperation; tourism cluster; JEL